2012
DOI: 10.1159/000341120
|View full text |Cite
|
Sign up to set email alerts
|

Does Chinese Herb Nephropathy Account for the High Incidence of End-Stage Renal Disease in Taiwan?

Abstract: Background: The incidence of end-stage renal disease (ESRD) in Taiwan ranks highest in the world, but the incidence of Chinese herb nephropathy (CHN) is unknown in this country where Chinese herb use is common. Methods: The etiologies of incident ESRD cases from 2000 to 2004 in a single tertiary referral medical center in Taiwan were independently reviewed by two nephrologists through medical records and telephone interview. Patients with obvious causes of ESRD were not diagnosed with CHN, in spite of Chinese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Long-term ingestion of herbal formula known or suspected to contain AAs is one of the prominent risk factors for developing AAN (Jia et al, 2005; Vervaet et al, 2017). Although the sale and use of AA-containing products are banned or restricted in most of the countries (Krell and Stebbing, 2013), AAN induced by numerous herbal remedies and products are still reported from all over the world (Lord et al, 1999; Yang et al, 2006; Debelle et al, 2008; Shaohua et al, 2010; Wu et al, 2012; Vaclavik et al, 2014; Ban et al, 2018).…”
Section: Aristolochic Acid-induced Adverse Reactionsmentioning
confidence: 99%
“…Long-term ingestion of herbal formula known or suspected to contain AAs is one of the prominent risk factors for developing AAN (Jia et al, 2005; Vervaet et al, 2017). Although the sale and use of AA-containing products are banned or restricted in most of the countries (Krell and Stebbing, 2013), AAN induced by numerous herbal remedies and products are still reported from all over the world (Lord et al, 1999; Yang et al, 2006; Debelle et al, 2008; Shaohua et al, 2010; Wu et al, 2012; Vaclavik et al, 2014; Ban et al, 2018).…”
Section: Aristolochic Acid-induced Adverse Reactionsmentioning
confidence: 99%
“…27 More female Chinese herbal nephropathies have been diagnosed. 28 In the study by Chang et al, the authors report that the use of Chinese herbs, especially if they contain aristolochic acid or compound analgesics, may contribute to the development of urothelial carcinoma. 29 A population-based study also revealed that the use of aristolochic acid-containing Chinese herbal products is associated with a dose-dependent increased risk of urinary tract cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Currently known as aristolochic acid nephropathy [16], this endemic disease may not only result in end-stage renal disease (ESRD), but also UTUC [8,17,18,19]. Therefore, it is no surprise that a consistent linkage between ESRD patients and their increased urothelial carcinoma (UC) risks has been repeatedly reported in AA-endemic area [20,21], with a general sequential order being UC after ESRD [22,23].…”
Section: The Link Between Aa and Utucmentioning
confidence: 99%